From abstract to concrete: some tips for developing an empirical stock–flow consistent model - Marco Veronese Passarella (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
The main purpose of this paper is to show how a simple (medium-scale) empirical stock–flow consistent dynamic model can be developed from scratch. Eurostat data and conventional statistical packages (notably EViews, Excel and R) are used. On the theoretical side, the work builds upon the pioneering work of Godley/Lavoie (2007). Sectoral transactions–flow matrices and balance sheets are explicitly modelled and their evolution over time under different scenarios is analysed. On the empirical side, the model draws upon the applied work of Burgess et al. (2016). The case of Italy is considered, but the model can be replicated for other countries. Eurostat annual data (from 1995 to 2016) are used to estimate or calibrate most model parameter values (for example, consumption function and housing investment parameters). Remaining parameters are borrowed from the available literature or taken from a range of realistic values (for example, weight on past errors in agents' expectations). The model is then used to impose and compare alternative scenarios for Italian sectoral financial balances, based on different shocks to government spending.
Keywords: E21; E22; E25; E37; 330; sectoral balances; flow of funds; macro modelling; Italian economy